Effects of C/N controlled periphyton based organic farming of freshwater prawn on water quality parameters and biotic factors - Rubaiya Pervin; Md. Rezoanul Haque; Mahmuda Akter (Journal of Fisheries, 2014)
The effects of C:N controlled periphyton based organic farming of freshwater prawn on water quality parameters and biotic factors were investigated. The experiment had two treatments: T1 and T2 each with three replications. Stocking density was maintained at 20,000 juveniles ha-1. In T1, only commercially available prawn feed was applied and in T2, a locally formulated and prepared feed containing 24% crude protein with C:N ratio close to 20 was used, and maize flour and bamboo side shoots were provided for maintaining C:N ratio 20. Mean values of water quality parameters did not vary significantly (P>0.05) between treatments. Periphytic biomass in terms of dry matter, ash free dry matter (AFDM) and chlorophyll a showed significant difference (P<0.05) among different sampling months. Individual harvesting weight, individual weight gain, specific growth rates, gross and net yields of prawn were significantly higher (P<0.05) in T2 than T1. Therefore, it was concluded that freshwater prawn might consume periphyton biomass in C:N controlled periphyton based organic farming practices resulted a significantly (P<0.05) higher production of freshwater prawn than traditional farming.